Throughput/area optimised pipelined architecture for elliptic curve crypto processor. Issue 5 (25th March 2019) - Imran, Malik; Rashid, Muhammad; Jafri, Atif Raza; Kashif, Muhammad
Abstract : A pipelined architecture is proposed in this work to speed up the point multiplication in elliptic curve cryptography (ECC). This is achieved, at first; by pipelining the arithmetic unit to reduce the critical path delay. Second, by reducing the number of clock cycles (latency), which is achieved through careful scheduling of computations involved in point addition and point doubling. These two factors thus, help in reducing the time for one point multiplication computation. On the other hand, the small area overhead for this design gives a higher throughput/area ratio. Consequently, the proposed architecture is synthesised on different FPGAs to compare with the state‐of‐the‐art. The synthesis results over GF(2 m ) show that the proposed design can work up to a frequency of 369, 357 and 337 MHz when implemented for m = 163, 233 and 283 bit key lengths, respectively, on Virtex‐7 FPGA. The corresponding throughput/slice figures are 42.22, 12.37 and 9.45, which outperform existing implementations.